2013
DOI: 10.1016/j.pss.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Periodic bursts of Jovian non-Io decametric radio emission

Abstract: During the years 2000–2011 the radio instruments onboard Cassini, Wind and STEREO spacecraft have recorded a large amount of the Jovian decametric radio emission (DAM). In this paper we report on the analysis of the new type of Jovian periodic radio bursts recently revealed in the decametric frequency range. These bursts, which are non-Io component of DAM, are characterized by a strong periodic reoccurrence over several Jovian days with a period ≈1.5% longer than the rotation rate of the planet's magnetosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…in the extended Io torus. In the decameter range, Panchenko et al (2013) observed radio arcs resembling Io's in subcorotation with the same period as that observed by Steffl et al (2006) in the torus, and interpreted as the beating of the System III (internal) and IV (torus perturbations) periods. The beating originates from a peak of the hot electron population density near 290…”
Section: Non-io Emissions and Rotational Dynamicssupporting
confidence: 65%
“…in the extended Io torus. In the decameter range, Panchenko et al (2013) observed radio arcs resembling Io's in subcorotation with the same period as that observed by Steffl et al (2006) in the torus, and interpreted as the beating of the System III (internal) and IV (torus perturbations) periods. The beating originates from a peak of the hot electron population density near 290…”
Section: Non-io Emissions and Rotational Dynamicssupporting
confidence: 65%
“…Kaiser 1993;Kaiser et al 1996). Panchenko et al (2013) have shown that non-Io decametric emissions exhibit periodic bursts with periods about 1.5% longer than the rotation rate of Jupiter and that are strongly correlated with solar wind pressure increases, typically occurring every ∼ 25 days. Additionally, Louarn et al (1998Louarn et al ( , 2000Louarn et al ( , 2001Louarn et al ( , 2014 have used Galileo observations of hectometric radiation, narrow- Gurnett et al (2002) band kilometric radiation, and trapped continuum radiation to study the dynamics of the magnetosphere.…”
Section: Auroral Radio Emissionsmentioning
confidence: 99%
“…Bright, transient, nonthermal emission from Jupiter and Io also occur at <40 MHz (Cecconi et al 2012;Panchenko et al 2013); however, at 40-120 MHz, the antenna temperature observed by an instrument like that proposed for DARE is only ∼1 mK for Jupiter (Zarka 2004). Jupiter, and other astronomical sources such as Cas A (similarly beam-diluted), may introduce low-level spectral effects due to scattering off the spacecraft.…”
Section: Other Foregroundsmentioning
confidence: 99%